Spain's Eighteenth-Century Periodical Press. Antonio Valladares de Sotomayor and the Semanario Erudito. - Larriba, Elisabel (Dieciocho: Hispanic Enlightenment)
The article focuses on the figure of Antonio Valladares de Sotomayor, a prolific author of the 18th century in Spain, and his contribution to periodical press through the "Semanario Erudito." Valladares, who lived during the Enlightenment and faced censorship, stood out for his work as a humanist, philosopher, and editor, rescuing forgotten works and promoting the history of Spain. Madeline Sutherland-Meier's research offers a detailed view of his life and work, as well as the impact of the "Semanario Erudito" on the dissemination of knowledge in his time, highlighting the relevance of his focus on documented history versus fiction.